2000
DOI: 10.1038/71724
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac defects and renal failure in mice with targeted mutations in Pkd2

Abstract: PKD2, mutations in which cause autosomal dominant polycystic kidney disease (ADPKD), encodes an integral membrane glycoprotein with similarity to calcium channel subunits. We induced two mutations in the mouse homologue Pkd2 (ref.4): an unstable allele (WS25; hereafter denoted Pkd2WS25) that can undergo homologous-recombination-based somatic rearrangement to form a null allele; and a true null mutation (WS183; hereafter denoted Pkd2-). We examined these mutations to understand the function of polycystin-2, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
297
1
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(316 citation statements)
references
References 24 publications
11
297
1
7
Order By: Relevance
“…40). In addition to the malformations described previously 41,42 , homozygous mutant embryos showed right pulmonary isomerism, randomization of embryonic turning, heart looping and abdominal situs inversus. In Pkd2 -/-mice, Leftb and Nodal were not expressed in the left lateral plate mesoderm, and Ebaf was absent from the floor-plate 40 .…”
mentioning
confidence: 49%
“…40). In addition to the malformations described previously 41,42 , homozygous mutant embryos showed right pulmonary isomerism, randomization of embryonic turning, heart looping and abdominal situs inversus. In Pkd2 -/-mice, Leftb and Nodal were not expressed in the left lateral plate mesoderm, and Ebaf was absent from the floor-plate 40 .…”
mentioning
confidence: 49%
“…This result is consistent with studies in which transient small interference RNA-mediated inhibition of Pkhd1 in cholangiocytes resulted in shortening and decreased formation of cilia, 29 but spatial and environmental differences between in vivo tissues and in vitro cell culture may lead to different results. Mouse models with a deletion of Pkhd1 exon 40 44 and genetargeted mutations in Pkd2 that cause distinct liver and/or kidney cysts 33,45,46 do not exhibit defects in ciliary structure in the affected epithelial cells, suggesting that the failure of renal epithelia to assemble primary cilia may not be the only factor leading to cyst formation in the kidneys. For example, a recent study showed that disruption of the extracellular matrix protein laminin ␣5, which is a major component of the tubular and glomerular basement membranes, also produces cystic kidneys in Lama5 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 To produce mutant mice for Pkhd1, we designed a targeting construct disrupting its 15th coding exon (Figure 1). We found 620 embryonic stem cell colonies resistant to G418, with one (W4A5) identified by PCR screening using a pair of outside-construct and cassette-based primers.…”
Section: Mouse Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human PKD2 mutations are responsible for a large number of cases of autosomal dominant polycystic kidney disease (ADPKD) (Mochizuki et al, 1996) and null mutation of the murine ortholog Pkd2 is embryonic lethal. Pkd2 mutants exhibit severe cardio-vascular defects, and form cysts in developing nephrons and pancreatic duct (Wu et al, 2000). Morpholino-based loss of function of pkd2 also results in the formation of pronephric cysts during zebrafish development (Obara et al, 2006;Sun et al, 2004) and in the formation of severe edema and of dilated pronephric tubules in Xenopus (Tran et al, 2010).…”
Section: Introductionmentioning
confidence: 99%